Emotional Intelligence as a Moderator between Micromanagement Leadership and Employee Performance - Mishra, Namrata; Rajkumar, M.; Mishra, Rajiv (Prabandhan: Indian Journal of Management, 2022)
Today’s businesses work in a fast-paced, uncertain, and intensely competitive environment. In such circumstances, organizations depend on their leaders for better results. Leaders use different leadership styles to accomplish their tasks and achieve success. Micromanagement is one such type of leadership style, wherein leaders are overly focused on results, staff-controlling, issues handling, and making all choices on their own. Such constant observation and supervision of employees create an impact on their performance. On the other side, leaders with high emotional intelligence try to empathize with their team members and facilitate improving their performance by giving them constructive criticism. The present study proposed a theoretical framework by investigating the influence of micromanagement leadership on employee performance, and the moderating effect of emotional intelligence on the relationship between micromanagement leadership towards employee performance. This study also emphasized the implications for leaders, employees, and organizations, thereby formulating propositions that can act as a foundation for future empirical work.